Developing Critical Thinking in Female Teacher Candidates at SQU: A Predictive Model - Caroline D. Ladewig (Sultan Qaboos University, 2017)
The purpose of this paper was to articulate the way in which socio-cultural factors influence the propensity for critical thinking among female teacher candidates at Sultan Qaboos University (SQU) in Oman. The sample consisted of 274. Twelve independent variables were ascertained, relating to key Omani institutions and forms of socio-cultural capital. A significant model to predict critical thinking identified religious beliefs and practices, family support for a knowledge society, valuing individual qualities (motivation participation and learning outcomes) over other forms of capital, and the state's endorsement of the role of teachers as loyal civil servants and trusted agents of change. Implications for teacher education programs and future research are also presented.